2016
DOI: 10.1039/c6dt03454c
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and notable optical nonlinearities of ultrathin composite films derived from water-soluble Keggin-type polyoxometalates and water-insoluble phthalocyanine

Abstract: Composite films with the general formula (POM/CuTAPc) derived from water-soluble Keggin-type polyoxometalates (POMs = HPMoVO, HSiWO, HPMoO and HPWO) and water-insoluble 4,9,16,23-copper tetraaminophthalocyanine (denoted CuTAPc) are successfully fabricated by a layer-by-layer self-assembly technique and systematically characterized. The structure of the polyoxometalate anions in the multilayers is kept intact; the deposition amounts of POM and CuTAPc remain constant in every adsorption cycle of the composite fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…34 It is also concluded that the hybrid wherein Anderson type POM is coupled covalently to porphyrin through shorter bridge has an NLO response superior to the hybrid, wherein Anderson type POM is bonded via longer bridge to porphyrin, and the hybrid having two porphyrins connected to Anderson type POM shows more enhancement than the hybrid having single porphyrin fused to Anderson type POM. 32 Notably, the previous study showed that polyoxometalate having lower LUMO level (versus LUMO of porphyrin moiety) can act as electron acceptor making easy the transfer of electrons from porphyrin moieties (acting as electron donor to polyoxometalates), [32][33][34][35]38,39 and the resulting hybrids exhibit better optical nonlinearities. While the previous work is fruitful and interesting, the study on this new emerging porphyrinpolyoxometalates hybrid system is still quite limited and well understanding remains a challenge in view of structure− property relationship, therefore more effort in designing and synthesizing more new hybrids of different structures to study their NLO properties is necessary in both theoretical and practical point of view.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…34 It is also concluded that the hybrid wherein Anderson type POM is coupled covalently to porphyrin through shorter bridge has an NLO response superior to the hybrid, wherein Anderson type POM is bonded via longer bridge to porphyrin, and the hybrid having two porphyrins connected to Anderson type POM shows more enhancement than the hybrid having single porphyrin fused to Anderson type POM. 32 Notably, the previous study showed that polyoxometalate having lower LUMO level (versus LUMO of porphyrin moiety) can act as electron acceptor making easy the transfer of electrons from porphyrin moieties (acting as electron donor to polyoxometalates), [32][33][34][35]38,39 and the resulting hybrids exhibit better optical nonlinearities. While the previous work is fruitful and interesting, the study on this new emerging porphyrinpolyoxometalates hybrid system is still quite limited and well understanding remains a challenge in view of structure− property relationship, therefore more effort in designing and synthesizing more new hybrids of different structures to study their NLO properties is necessary in both theoretical and practical point of view.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As polyoxometalates are excellent electron acceptors, efforts have been driven to bond the polyoxometalate with porphyrins to get excellent nonlinear responses. Studies on the nonlinearity of a series of Keggin polyoxometalate-porphyrin sandwich compounds have informed that the auxiliary electron acceptors on the porphyrin ring cause to enhance the value of second order polarziability . Recently, our group , ,, has been interested in exploring third-order NLO properties of new porphyrin-polyoxometalates hybrid systems formed either by electrostatic or covalent bonding, and the results imply that such kind of hybrids are promising candidate materials for device applications in photonics and optoelectronics and high potential as lower power optical limiting materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 The unique properties of POMs, such as structural persistence, strong electron acceptance, reversible redox characteristics, adjustable band structure, environmental friendliness, easy preparation and low-cost, make it become a novel and important potential material for various battery (cell) fields. At present, the review on the research progress of POMs-based materials is mainly focused on the catalytic water oxidation, 37 photocatalysis, 38 supercapacitors and the photoelectric properties of POMs-based films, 39,40 but the application in the third generation of solar cells is rarely summarized or not updated in time. Based on our research work and combined with the latest literature survey, this paper reviews the research status and progress of POMs in the application of the third generation of solar cells and expects the utilization prospects of POMs, hoping to provide some valuable information for the basic research and practical application of related fields.…”
Section: Introductionmentioning
confidence: 99%